2013
DOI: 10.1134/s0006297913060084
|View full text |Cite
|
Sign up to set email alerts
|

Biogenesis, evolution, and functions of plant microRNAs

Abstract: This review focuses on the biological role of one class of plant small RNAs, ~22-nt microRNAs (miRNAs). The majority of plant miRNA targets are genes encoding the effector factors of cell signaling pathways. The regulation of their expression is necessary for both ontogenesis and rapid response of plants to biotic and abiotic stress factors. We also summarized current views on the biogenesis and evolution of plant miRNAs as well as the techniques used for their investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 104 publications
1
18
0
1
Order By: Relevance
“…Small RNAs are a class of non-coding RNAs that play vital roles in growth and development, signal transduction, biotic and abiotic stresses (Jones-Rhoades et al, 2006; Dalmay, 2010; Mohorianu et al, 2011; Zuo et al, 2012; Pashkovskiy and Ryazansky, 2013). Numerous studies have demonstrated that miRNAs were involved in the regulation of diverse physiological processes by repressing the expression of their target genes.…”
Section: Discussionmentioning
confidence: 99%
“…Small RNAs are a class of non-coding RNAs that play vital roles in growth and development, signal transduction, biotic and abiotic stresses (Jones-Rhoades et al, 2006; Dalmay, 2010; Mohorianu et al, 2011; Zuo et al, 2012; Pashkovskiy and Ryazansky, 2013). Numerous studies have demonstrated that miRNAs were involved in the regulation of diverse physiological processes by repressing the expression of their target genes.…”
Section: Discussionmentioning
confidence: 99%
“…As a novel type of regulatory factor, plant miRNAs play an important role in plant-pathogen interaction37. For instance, our previous work has shown that the miR396 family miRNAs target growth-regulating factor (GRF) genes.…”
Section: Discussionmentioning
confidence: 99%
“…MiRNAs are known to regulate gene expression either through mRNA cleavage, progressive mRNA decay, or translation inhibition (Llave et al 2002;Jin et al 2013;Pashkovskiy and Ryazansky 2013;Budak et al 2015a). In order to gain further insight into miRNA regulatory networks involved in drought stress response, targets of the putative miRNAs were predicted.…”
Section: Stress Induced Mirna Target Regulationmentioning
confidence: 99%
“…In plants, miRNAs are involved in a variety of processes, ranging from their own biogenesis to development and stress responses (Budak and Akpinar 2011;Sunkar et al 2012;Jin et al 2013;Pashkovskiy and Ryazansky 2013;Budak and Akpinar 2015;Budak et al 2015a). Several miRNAs have been identified in plants so far, including wheat, for which 293 mature miRNA sequences are deposited in the current release of miRBase (http://mirbase.org/), while some others are reported in various publications (Budak et al 2015b).…”
Section: Introductionmentioning
confidence: 98%